PENGARUH GENDER SEBAGAI PEMODERASI PENGEMBANGAN MODEL PERILAKU KONSUMEN HIJAU DI INDONESIA - M.F. Shellyana Junaedi (Faculty of Business and Economics Universitas Atma Jaya Yogyakarta, 2008)
This study examined the model development causal that can predict the green consumer behavior on organic food as green product. This study tested the influence of values orientation on environmental consciousness. This study also explained the effect of ecological knowledge, ecological affect, premium price and environment consciousness on green purchase intention. The role of gender as moderating variables on the causal model development. The analysis of 723 respondents all of those are people who influence and purchase their daily food. The result, based on path analysis using multi group structural equation modeling, indicated that the model tested had an acceptable fit. The idea implied in this research will be much help in resolving problem and decision making, connected to reinforce the green purchasing.Keywords: green consumer, attitude, behavior, organic food, gender